Photorefraction and in-situ optical cleaning in various types of LiNbO3 waveguides - Kirsch, Michelle; Kießler, Christian; Lengeling, Sebastian; Stefszky, Michael; Eigner, Christof; Herrmann, Harald; Silberhorn, Christine (Optics & Laser Technology)
Lithium niobate (LiNbO3) is a widely used material with several desirable physical properties, such as high second-order nonlinear optical and strong electro-optical effects. Thus LiNbO3 is used for various applications such as electro-optic modulation or nonlinear frequency conversion and mixing. But LiNbO3 also exhibits a strong photorefractive effect, which limits the intensity of the optical fields involved. Various approaches to reduce the photorefractive effect have been investigated, such as increasing the temperature, doping the crystal or using different waveguide designs in LiNbO3. Here, we present an analysis of the approach to increase the photorefractive damage threshold by using different waveguide designs. Contrary to previous claims and investigations, our SHG measurements revealed no significant difference in resistance to photorefractive damage when comparing conventional Ti-doped channel waveguides and Ti-doped diced ridge waveguides in LiNbO3. Furthermore, we have investigated the effect of photorefractive cleaning and curing using a light field at 532 nm. Here, we observe a reduction in the photorefractive effect at room temperature during and after SHG measurements, which is an easy alternative to conventional approaches.

SPDC single-photon source in Ti-indiffused diced ridge LiNbO3 waveguides - Kießler, Christian; Kirsch, Michelle; Lengeling, Sebastian; Herrmann, Harald; Silberhorn, Christine (Optics Continuum)
Stable and bright single photon sources are key components for future quantum applications. A simple fabrication method is an important requirement for such sources. Here, we present a single photon source based on diced ridge waveguides in titanium indiffused LiNbO 3 . These waveguides can be easily fabricated by combining planar titanium in-diffusion without lithographic patterning and easy-to-handle precision dicing. Such devices have the potential to generate high single photon rates because ridge structures are typically less prone to the photorefractive effect. We achieve waveguide propagation losses <0.4dBcm and a SHG conversion efficiency of about 81%Wcm 2 . Harnessing a type-0 SPDC process to generate 1550 nm photons, we obtain a SPDC brightness of 3⋅10 5 1s⋅mW⋅nm, with a heralding efficiency of η h =45% ( η h,wg =77.5% for the waveguide itself excluded setup losses) and a heralded second-order correlation function of g h 2 (0)<0.003 at low pump powers.

Fiber-coupled plug-and-play heralded single photon source based on Ti:LiNbO3 and polymer technology - Kießler, Christian; Conradi, Hauke; Kleinert, Moritz; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Optics Express)
A reliable, but cost-effective generation of single-photon states is key for practical quantum communication systems. For real-world deployment, waveguide sources offer optimum compatibility with fiber networks and can be embedded in hybrid integrated modules. Here, we present what we believe to be the first chip-size fully integrated fiber-coupled heralded single photon source (HSPS) module based on a hybrid integration of a nonlinear lithium niobate waveguide into a polymer board. Photon pairs at 810 nm (signal) and 1550 nm (idler) are generated via parametric down-conversion pumped at 532 nm in the LiNbO3 waveguide. The pairs are split in the polymer board and routed to separate output ports. The module has a size of (2 × 1) cm^2 and is fully fiber-coupled with one pump input fiber and two output fibers. We measure a heralded second-order correlation function of g_h(2)=0.05 with a heralding efficiency of η_h=3.5% at low pump powers
Keywords: Atomic and Molecular Physics; and Optics

On-Chip Quantum Communication Devices - Trenti, Alessandro; Achleitner, Martin; Prawits, Florian; Schrenk, Bernhard; Conradi, Hauke; Kleinert, Moritz; Incoronato, Alfonso; Zanetto, Francesco; Zappa, Franco; Luch, Ilaria Di; Cirkinoglu, Ozan; Leijtens, Xaveer; et al. (Journal of Lightwave Technology)
Keywords: General Engineering

Nonlinear waveguides for integrated quantum light source - Domeneguetti, Renato R.; Conradi, Hauke; Kleinert, Moritz; Kießler, Christian; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas Schou; Gehring, Tobias (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference)
We experimentally investigate the generation of continuous-wave optical squeezing from a titanium-indiffused lithium niobate waveguide resonator at low and high frequencies. The device promises integration with different platform chips for more complex optical systems.
Keywords: Optical systems; Polymer waveguides; Quantum key distribution; Quantum light sources; Squeezed states; Waveguides